EVALUASI IMPLEMENTASI SUPERVISI AKADEMIK TERHADAP KINERJA GURU SMPN 1 KABUPATEN BIMA - Sahrul, Sahrul; Sari, Ardiana Vita Ratna; Kusbiantari, Dyah; Azmi, Ahnaf Tsabitul; Sani, Annisa Aulia; Uyun, Muhammad Fatahul; Barus, Robi Agape (Dharmas Education Journal (DE_Journal), 2024)
The research aims to determine the performance of teachers in academic supervision by supervisors, school principals, senior teachers, or mentors. This study was conducted at SMPN 1 Sape-Bima in the year 2023, which has implemented the independent curriculum. It is qualitative research conducted in several stages: evaluation, planning, observation, interviews, observation, and document studies. The research is used to understand and identify the academic supervision performance of teachers carried out by supervisors, school principals, and senior teachers who are related or involved in academic supervision to enhance teacher performance. It employs a good strategy to connect theory and practice. The study seeks to analyze and describe Academic Supervision in Improving Teacher Performance Motivation to create Learning Devices. The population of this study is the teachers of SMPN 1 Sape-Bima who have implemented the independent curriculum. The research findings indicate that supervision is conducted twice a year at the beginning of each odd and even semester, and it is subject-specific. However, before the supervision takes place, all teachers are informed by the school principal two weeks before the implementation begins. Supervision obstacles include instances where teachers are not present at school during the supervision due to not having teaching hours on the day of supervision and limited time due to the large number of teachers.